Immunisation coverage and its determinants among children aged 12-23 months in Atakumosa-west district, Osun State Nigeria: a cross-sectional study - Elizabeth B. Adedire; Ikeoluwapo Ajayi; Olufunmilayo I. Fawole; Olufemi Ajumobi; Simon Kasasa; Peter Wasswa; Patrick Nguku (BMC, 2016)
Abstract Background Routine immunisation (RI) contributes immensely to reduction in mortality from vaccine preventable diseases (VPD) among children. The Nigerian Demographic and Health Survey, 2008 revealed that only 58 % of children in Osun State had received all recommended vaccines, which is far below World Health Organization (WHO) target of 80 %. We therefore, assessed RI uptake and its determinants among children in Atakumosa-west district of Osun State. Methods Atakumosa-west district has an estimated population of 90,525 inhabitants. We enrolled 750 mothers of children aged 12-23 months in this cross-sectional study. Semi-structured questionnaires were used to obtain data on socio-demographic characteristics, knowledge of mothers on RI, history of RI in children and factors associated with full RI uptake. A fully-immunised child was defined as a child who had received one dose of Bacillus-Calmette-Guerin, three doses of Oral-Polio-Vaccine, three doses of Diptheria-Pertusis-Tetanus vaccine and one dose of measles vaccine by 12 months of age. We tested for the association between immunisation uptake and its likely determinants using multivariable logistic regression at 0.05 level of significance and 95 % confidence Interval (CI). Results Mean ± (SD) age of the mothers and children were 27.9 ± 6.1 years and 17.2 ± 4.0 months, respectively. About 94 % (703/750) of mothers had received antenatal care (ANC) and 63.3 % (475) of the children possessed vaccination cards. Seventy-six percent (571/750) had good knowledge of RI and VPD. About 58 % (275/475) of children who possessed vaccination card were fully-immunised. Mothers antenatal care attendance (aOR = 3.3, 95 % CI = 1.1-8.3), maternal tetanus toxoid immunisation (aOR = 3.2, 95 % CI = 1.1-10.0) access to immunisation information (aOR = 1.8, 95 % CI = 1.1-2.5) and mothers having good knowledge of immunisation (aOR = 2.4, 95 % CI = 1.6-3.8) were significant determinants of full immunisation. Conclusions Routine immunisation uptake was still below WHO target in the study area. Encouraging mothers to attend antenatal care and educational interventions targeted at rural mothers are recommended to improve vaccination status of children in the rural communities.